Comparison of liver scintigraphy and the liver-spleen contrast in Gd-EOB-DTPA-enhanced MRI on liver function tests - Hiroshige Mori (Nature Portfolio, 2021)
Abstract The liver-spleen contrast (LSC) using hepatobiliary-phase images could replace the receptor index (LHL15) in liver scintigraphy; however, few comparative studies exist. This study aimed to verify the convertibility from LSC into LHL15. In 136 patients, the LSC, not at 20 min, but at 60 min after injecting gadolinium-ethoxybenzyl-diethylenetriaminepentaacetic acid was compared with the LHL15, albumin–bilirubin (ALBI) score, and the related laboratory parameters. The LHL15 was also compared with their biochemical tests. The correlation coefficients of LSC with LHL15, ALBI score, total bilirubin, and albumin were 0.740, –0.624, –0.606, and 0.523 (P < 0.00001), respectively. The correlation coefficients of LHL15 with ALBI score, total bilirubin, and albumin were –0.647, –0.553, and 0.569 (P < 0.00001), respectively. The linear regression equation on the estimated LHL15 (eLHL15) from LSC was eLHL15 = 0.460 · LSC + 0.727 (P < 0.00001) and the coefficient of determination was 0.548. Regarding a contingency table using imaging-based clinical stage classification, the degree of agreement between eLHL15 and LHL15 was 65.4%, and Cramer's V was 0.568 (P < 0.00001). Therefore, although the LSC may be influenced by high total bilirubin, the eLHL15 can replace the LSC as an index to evaluate liver function.